Heart Rate–Based Prediction of Fixed Blood Lactate Thresholds in Professional Team-Sport Players. Issue 10 (October 2015) - Garcia-Tabar, Ibai; Llodio, Iñaki; Sánchez-Medina, Luis; Ruesta, Maite; Ibañez, Javier; Gorostiaga, Esteban M.
Abstract : Abstract: Garcia-Tabar, I, Llodio, I, Sánchez-Medina, L, Ruesta, M, Ibañez, J, and Gorostiaga, EM. Heart rate–based prediction of fixed blood lactate thresholds in professional team-sport players. J Strength Cond Res 29(10): 2794–2801, 2015—The aim of this study was to investigate whether the speed associated with 90% of maximal heart rate (S90%HRmax) could predict speeds at fixed blood lactate concentrations of 3 mmol·L −1 (S3mM) and 4 mmol·L −1 (S4mM). Professional team-sport players of futsal ( n = 10), handball ( n = 16), and basketball ( n = 10) performed a 4-stage discontinuous progressive running test followed, if exhaustion was not previously achieved, by an additional maximal continuous incremental running test to attain maximal heart rate (HRmax). The individual S3mM, S4mM, and S90%HRmax were determined by linear interpolation. S3mM (11.6 ± 1.5 km·h −1 ) and S4mM (12.5 ± 1.4 km·h −1 ) did not differ ( p > 0.05) from S90%HRmax (12.0 ± 1.2 km·h −1 ). Very large significant ( p < 0.001) relationships were found between S90%HRmax and S3mM ( r = 0.82; standard error of the estimates [SEE] = 0.87 km·h −1 ), as well as between S90%HRmax and S4mM ( r = 0.82; SEE = 0.87 km·h −1 ). S3mM and S4mM inversely correlated with %HRmax associated with running speeds of 10 and 12 km·h −1 ( r = 0.78–0.81; p < 0.001; SEE = 0.94–0.87 km·h −1 ). In conclusion, S3mM and S4mM can be accurately predicted by S90%HRmax in professional team-sport players.